Implementasi Hot Pack untuk Peningkatan Suhu Tubuh pada Pasien Hipotermi Post Operasi dengan Anestesi Spinal di RSUD Cilacap - Darojattulloh Darojattulloh; Dwi Novitasari; Tri Sumarni (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Hypothermia is a common complication in postoperative patients with spinal anesthesia, which can increase the risk of bleeding, delay healing, and reduce patient comfort. One non-pharmacological intervention to prevent this condition is the use of Hot Packs. This community service activity aims to implement Hot Packs as an effort to increase body temperature in postoperative hypothermic patients with spinal anesthesia at Cilacap Regional Hospital. The implementation method involved 30 participants selected through screening of patients with body temperatures <36°C. The intervention was carried out by placing a Hot Pack on the back of the neck for 15 minutes, then the patient's body temperature was measured using a tympanic thermometer before and after the intervention. The analysis results showed a significant increase in body temperature, from an average of 35.2°C before the intervention to 36.0°C afterward, with an average difference of 0.777°C (SD 0.467°C) and a p value = 0.000. These findings prove that the implementation of Hot Packs is effective in increasing the body temperature of hypothermic patients after spinal anesthesia. This intervention is considered simple, economical, and easy to apply by health workers in daily clinical practice.